2003
DOI: 10.1093/humrep/deg018
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid decreases the viability of mouse blastocysts in vitro

Abstract: This is the first evidence that retinoic acid induces cell death (apoptosis) and inhibits cell proliferation in mouse blastocysts. This results in the retardation of early postimplantation blastocyst development and subsequent blastocyst death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 37 publications
4
40
4
Order By: Relevance
“…In cultured mouse blastocysts, the antiproliferative and pro-apoptotic effects of 10 µm ATRA were mainly targeted to the ICM (Huang et al 2005). These studies did not contain protein in the medium and the high supraphysiological concentrations of ATRA used may explain why these detrimental effects of 10 µm ATRA in mice (Huang et al 2003) differ to the results obtained in the present study. In addition, there are important species-specific differences, because RARβ mRNA expression has been shown in mice (Wu et al 1981), but not in bovine blastocysts (Mohan et al 2001).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In cultured mouse blastocysts, the antiproliferative and pro-apoptotic effects of 10 µm ATRA were mainly targeted to the ICM (Huang et al 2005). These studies did not contain protein in the medium and the high supraphysiological concentrations of ATRA used may explain why these detrimental effects of 10 µm ATRA in mice (Huang et al 2003) differ to the results obtained in the present study. In addition, there are important species-specific differences, because RARβ mRNA expression has been shown in mice (Wu et al 1981), but not in bovine blastocysts (Mohan et al 2001).…”
Section: Discussioncontrasting
confidence: 74%
“…In the mouse, exposure of blastocysts to excessATRA directly affects the ICM (Huang et al 2005), leading to adverse effects on development (Huang et al 2001(Huang et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that overexposure (48 h) of cattle oocytes to 9-cis-RA prior to fertilization reduced blastocyst rates, in contrast to oocytes incubated for 24 h with 9-cis RA either during meiotic inhibition or in vitro maturation [11,14,15]. The detrimental effects of high dosage were reported by Huang et al [16] in mice embryos exposed for 24 h to 10 mM ATRA. These authors found antiproliferative and pro-apoptotic effects that mainly targeted the ICM [17].…”
Section: Discussionmentioning
confidence: 88%
“…Most studies on retinoids have focused on later stages of embryonic development, although exposure of zygotes to RA during early embryonic development yields anomalies during pre-gastrulation and organogenesis (Rutledge 1997). Recently, RA treatment during the pre-implantation period in the mouse (Huang et al 2001(Huang et al , 2003 was shown to cause developmental retardation, inhibition of cell proliferation and induction of apoptosis. In previous reports, development of blastocysts to term was not analysed (Shaw et al 1995, Whaley et al 1997, Eberhardt et al 1999, and the precise stage (oocyte, embryo or both) during which retinoids exerted their effects was not determined.…”
Section: Embryos Transferred Pregnancy (%)mentioning
confidence: 99%